2011
DOI: 10.1074/jbc.m111.281675
|View full text |Cite
|
Sign up to set email alerts
|

A1Ao-ATP Synthase of Methanobrevibacter ruminantium Couples Sodium Ions for ATP Synthesis under Physiological Conditions

Abstract: Background: An enigma in the bioenergetics of methanogens is how the generation of proton and sodium gradients are used to synthesize ATP. Results: Purified methanogen ATP synthase was stimulated by sodium ions that also provided pH-dependent protection against DCCD. Conclusion:Methanobrevibacter ruminantium harbors an A-type enzyme with the ability to switch between sodium ions and protons. Significance: ATP synthesis by methanogens depends on the environmental conditions that prevail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 69 publications
(69 reference statements)
0
36
0
Order By: Relevance
“…strain AbM4 (Table 2). Monensin, a sodium ionophore, and 2-bromoethanesulfonic acid (BES), an analogue of methyl-coenzyme M, are potent inhibitors of methanogens (34). Using monensin (1 M) or BES (30 M), nearly complete inhibition, i.e., Ͼ85% reduction of growth, was observed for both strains (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…strain AbM4 (Table 2). Monensin, a sodium ionophore, and 2-bromoethanesulfonic acid (BES), an analogue of methyl-coenzyme M, are potent inhibitors of methanogens (34). Using monensin (1 M) or BES (30 M), nearly complete inhibition, i.e., Ͼ85% reduction of growth, was observed for both strains (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 92%
“…Methanococcus maripaludis strain S2 is a well-characterized genetically tractable methanogen that can be grown in the absence of H 2 and CO 2 using formate (27)(28)(29)(30)(31)(32). M. maripaludis grows quickly to high cell densities in contrast to slowly growing rumen isolates, such as Methanobrevibacter ruminantium M1, where cell densities are low (33,34). Both methanogens are typically grown using anaerobic culturing techniques in 5-ml or greater culture volumes using appropriately sealed and pressurized glass tubes, which is incompatible with modern high-throughput screening techniques for drug discovery and phenotypic analysis (35).…”
mentioning
confidence: 99%
“…Further, the A 1 A 0 ATPase/synthases studied among the members of the groups Methanobacteriales/Methanococcales have clearly been shown to pump Na + (McMillan et al, 2011;Mulkidjanian et al, 2008). In contrast, the cytochrome-containing methanogens in the Methanosarcinales have Mtr complexes, but also have steps that pump protons (Schlegel & Müller, 2013;Thauer et al, 2008), and evidence has favoured H + pumping by the ATPases in these organisms (Müller et al, 1999;Pisa et al, 2007).…”
Section: Adaptation To High Proton Concentrationsmentioning
confidence: 99%
“…In Table 3, partial sequences of the AtpC/K are aligned, and residues critical to Na + binding in the Methanobacteriales/Methanococcales (Grüber et al, 2014;McMillan et al, 2011) are indicated in bold. Also shown in bold are residues in the M. acetivorans sequence that are considered crucial to being able to bind either Na + or H + .…”
Section: Adaptation To High Proton Concentrationsmentioning
confidence: 99%
“…A switch from Na 1 to H 1 pumping has been observed for the ATP synthases from Propionigenium modestum and Methanobrevibacter ruminantium at low pH and low levels of Na 1 (47,48). This can be explained by the weak H 1 -selectivity of these ATP synthases as demonstrated by Krah and coworkers (49).…”
Section: The Possibility Of Na 1 Being a Coupling Ion In Complex Imentioning
confidence: 81%